2015
DOI: 10.19030/tlc.v12i1.9068
|View full text |Cite
|
Sign up to set email alerts
|

Visual Inspirations: The Pedagogical And Cultural Significance Of Creative Posters In The Art Classroom

Abstract: Creative posters in the classroom can inspire students to become engaged and motivated in learning art. Within the classroom, there are many places to put posters so that students can read them (especially when they get bored in the classroom) - on the cabinets, near the chalkboard, on the teachers desk and any spare space on the wall.There is cultural significance for using creative posters in the classroom; like advertising - the posters operate on a cultural level to provide symbolic associations between im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…With the teaching of activity-based posters, the success of the students in the experimental group are similar to the results of the researches conducted by Mulnix & Penale [44], Bracher et al [17], Berry ve Nayman [42], Chaznava et al [23], Brown & Burroughs [51], Tanner & Chapmen [28], Hasio [39] and Eker [34]. It can be stated that making posters in activity and presenting them to friends in class can contribute to meaningful learning by constructing self-information with teacher guidance and providing effective participation.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…With the teaching of activity-based posters, the success of the students in the experimental group are similar to the results of the researches conducted by Mulnix & Penale [44], Bracher et al [17], Berry ve Nayman [42], Chaznava et al [23], Brown & Burroughs [51], Tanner & Chapmen [28], Hasio [39] and Eker [34]. It can be stated that making posters in activity and presenting them to friends in class can contribute to meaningful learning by constructing self-information with teacher guidance and providing effective participation.…”
Section: Resultssupporting
confidence: 82%
“…When students prepare and present a poster about unit topics in the learning process, they reconstruct the learned topics in their minds, thus they enhance academic achievement [34]. As a result, the students move their minds and they realize meaningful learning thanks to activity based posters [39].The students have in-depth knowledge about a subject through the teaching conducted with the activity based on poster. In addition, they are more effective and successful in their activities when they are active rather than the other methods [44].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this result, the researcher rejected the second hypothesis and concluded that digital posters had a significant effect on the engagement of EFL students. This result goes along with Hasio's (2015) contention that posters help students engage in learning. Moreover, this result might find support in the findings of some studies (Angelini, 2014;Cook, 2013;Cook & Fenn, 2013;Kinikin & Hench, 2012;Rushton et al, 2014) which found posters (whether traditional or digital) to be helpful in improving student engagement.…”
Section: Discussionsupporting
confidence: 58%
“…Books, publications, crafts, CDs, films, an fashion design provide the public with a wealth of cultural options. By transforming "culture" into "creativity" and attaching it to products, the relationship between conditioned and purpose-oriented objects and people extends outward from the core according to the cultural connotation and the product's own characteristics, forming a "benefit" type commodity with both use and psychological function [4,5]. e core concept of cultural creative products lies in culture and creativity, which is the materialized expression of human wisdom and inspiration.…”
Section: Definition Of Cultural and Creative Productsmentioning
confidence: 99%